2010
DOI: 10.1051/0004-6361/200913402
|View full text |Cite
|
Sign up to set email alerts
|

Properties of dust in the high-latitude translucent cloud L1780

Abstract: Context. Lynds 1780 is a high-latitude cloud where, based on 2MASS, the maximum visual extinction is A max V = 4 mag at a resolution of 3 . In LDN1780, increased far-infrared (FIR) emissivity of dust grains has been observed, and the infrared emission is found to peak at different locations at different wavelengths. Aims. By modelling the FIR observations, we try to quantify spatial variations of dust properties and to determine to what extent the observations could be affected by the asymmetry of the heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Increased FIR and submillimetre opacity has been reported by many authors (Kramer et al 2003;Lehtinen et al 2004;del Burgo & Laureijs 2005;Ridderstad & Juvela 2010;Bernard et al 2010;Suutarinen et al 2013, etc.). One famous example is the Taurus filament L1506, for which the models of Stepnik et al (2003) suggested an increase by more than a factor of three.…”
Section: Comparison With Other Studiesmentioning
confidence: 69%
“…Increased FIR and submillimetre opacity has been reported by many authors (Kramer et al 2003;Lehtinen et al 2004;del Burgo & Laureijs 2005;Ridderstad & Juvela 2010;Bernard et al 2010;Suutarinen et al 2013, etc.). One famous example is the Taurus filament L1506, for which the models of Stepnik et al (2003) suggested an increase by more than a factor of three.…”
Section: Comparison With Other Studiesmentioning
confidence: 69%
“…The shorter wavelengths are more sensitive to temperature differences in the thin surface layers of the clouds and can trace variations in the heating radiation field or in the relative abundance of small and large grains (Laureijs et al 1989;Bernard et al 1992;Ridderstad & Juvela 2010). Therefore, these data can give further clues to the nature and the formation process of the clumps.…”
Section: Comparison With Other Infrared Datamentioning
confidence: 99%
“…Increased far-infrared and submillimetre opacity has been reported by many authors (Kramer et al 2003;Lehtinen et al 2004;del Burgo & Laureijs 2005;Ridderstad & Juvela 2010;Bernard et al 2010;Suutarinen et al 2013, etc.). One famous example is the Taurus filament L1506, for which the models of Stepnik et al (2003) suggested an increase by more than a factor of three.…”
Section: Comparison With Other Studiesmentioning
confidence: 75%